Building Food Resilience Against Floods: A Systematic Review of Absorptive, Adaptive and Transformational Strategies - Handayani, Naniek Utami; Ulkhaq, M. Mujiya; Sari, Diana Puspita; Mahachandra, Manik; Salsabila, Sheila Syifa (Journal of Ecohumanism, 2025)
Food resilience in flood-prone areas is a growing concern due to the increasing frequency and severity of floods caused by climate change. Floods can damage agricultural systems, disrupt supply chains, and lead to food insecurity, especially in vulnerable regions, including developing countries. This study then aims to identify and evaluate strategies to enhance food resilience in flood-prone areas by synthesizing existing research into absorptive, adaptive, and transformational capacities. It also seeks to develop an integrated framework to address short- and long-term food security challenges. A systematic literature review (SLR) was conducted following the PRISMA framework. The Scopus database was used to identify 325 articles published between 2010 and 2024. After a rigorous screening and eligibility process, 38 studies were selected for thematic and scientometric analysis to identify trends, methodologies, and strategies. The findings highlight three key resilience capacities: absorptive, adaptive, and transformational. Absorptive capacity focuses on minimizing immediate impacts through water management and drainage infrastructure. Adaptive capacity emphasizes medium-term adjustments, including diversified crops, Climate-smart agriculture, and improved supply chains. Transformational capacity addresses long-term structural reforms, such as biotechnology applications and integrated farming systems. Combining these strategies offers a holistic approach to building sustainable food systems resilient to floods. Addressing food security in flood-prone areas requires a proactive, multi-dimensional approach that incorporates absorptive, adaptive, and transformational capacities. The integrated framework developed in this study provides insights for policymakers, researchers, and stakeholders to create sustainable and resilient food systems amid climate variability and flood risks.